Zwischen Autobiographie und Fiktion: neue literarische Schreibweisen bei Felicitas Hoppe, Charlotte Roche, Stephan Wackwitz und David Wagner - Haberlah, Gesine (2016)
This thesis examines forms of autobiographical writing in the 21st century which are located at the intersection of autobiography and fiction. The literary sources selected question established genre boundaries, while also reflecting contemporary cultural discourses and creating particular images of their authors. My analysis investigates the new literary strategies emerging in Charlotte Roche’s Schoßgebete (2011), Stephan Wackwitz’s Ein unsichtbares Land (2003), Felicitas Hoppe’s Hoppe (2012) and David Wagner’s Leben (2012) in order to identify how texts such as these combine autobiography and fiction.